Innovation Capability as Mediator between Competence, Emotional Intelligence, Support, and Lecturer Performance in Indonesia - Abdilah, Luluh; M. Sidik Priadana; Juniarti, Atty Tri (Jurnal Ilmiah Manajemen Kesatuan, 2025)
This study investigates the mediating role of innovation capability in the relationship between organizational support, lecturer competence, and emotional intelligence on lecturer performance. Unlike previous research that emphasized only direct relationships, this study introduces innovation capability as a mediating mechanism, providing a novel perspective on how innovation strengthens lecturer performance. The research focuses on certified lecturers from private universities under the coordination of LLDIKTI Region IV in Bodetabek (Bogor, Depok, Tangerang, and Bekasi), Indonesia, a context that remains underexplored compared to public universities. Using a survey method, data were collected through questionnaires and interviews from a minimum sample of 354 certified lecturers, selected from a population of 3,048. The data were analyzed using Structural Equation Modeling (SEM) with LISREL 8, supported by descriptive analysis. Results show that lecturer competence has the strongest impact on innovation capability (29.44%), followed by organizational support (23.35%) and emotional intelligence (20.92%). Collectively, these variables explain 73.71% of the variance in innovation capability, which in turn significantly enhances lecturer performance, contributing 83.05%. The findings highlight the strategic role of fostering innovation capability to strengthen lecturer performance and competitiveness in the era of Industrial Revolution 4.0.